1987
DOI: 10.1017/s0030605300026600
|View full text |Cite
|
Sign up to set email alerts
|

The volcano rabbit—a shrinking distribution and a threatened habitat

Abstract: The first systematic search for the volcano rabbit, a Mexican endemic, found no evidence of the species outside the central region of the transverse neovolcanic axis around Mexico City, and reveals that the rabbit has now disappeared from areas of this central zone where it has been reported in the recent past. It depends for its survival on the pine forest—bunch grass ecosystem, and this is being destroyed by conversion to agriculture, over-grazing, fire-burns, poor forestry management and encroaching propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 1 publication
2
8
0
3
Order By: Relevance
“…The total rabbit population appears to be declining and some small isolated local populations may become extinct if the distribution range shrinks further. The size of the geographic range of the Amami rabbit estimated here is close to that of the volcano rabbit (280 sq km) ( Hoth et al , 1987 ; Fa & Bell, 1990). Both of these species retain primitive morphological characteristics among lagomorph species ( Chapman & Flux, 1990) and their distribution appears to have been shrinking ( Velazquez, 1994).…”
Section: Discussionsupporting
confidence: 66%
“…The total rabbit population appears to be declining and some small isolated local populations may become extinct if the distribution range shrinks further. The size of the geographic range of the Amami rabbit estimated here is close to that of the volcano rabbit (280 sq km) ( Hoth et al , 1987 ; Fa & Bell, 1990). Both of these species retain primitive morphological characteristics among lagomorph species ( Chapman & Flux, 1990) and their distribution appears to have been shrinking ( Velazquez, 1994).…”
Section: Discussionsupporting
confidence: 66%
“…3), coinciding with the limit of visibility and reduced audibility from the ranger station caused by a large east-west ridge. Previous studies have also identified the negative effect of hunting pressure on volcano rabbits (Hoth et al, 1987;Velazquez, 1989;Fa & Bell, 1990;Fa et al, 1992).…”
Section: Discussionmentioning
confidence: 97%
“…The volcano rabbit is considered endangered (SEMARNAT, 2010;IUCN, 2017). It is threatened by the loss and fragmentation of its habitat (Hoth et al, 1987;Velázquez et al, 2011), introduced species (dogs and cats), hunting, and more recently, climate change (López et al, 1996;Anderson et al, 2009). The main causes for the loss of habitat are anthropogenic fires, livestock grazing, and logging (López et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…comm.). There is also anecdotal information regarding sightings in the 1980s, but no evidence was found during a field study in 1987 (Hoth et al, 1987). In 1998, Ceballos et al (1998 reported finding dung pellets attributable to the species but no further details were given.…”
Section: Introductionmentioning
confidence: 99%